2015
DOI: 10.1177/1934578x1501000673
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Components of Four Essential Oils in Aromatherapy Recipe

Abstract: This study focused on characterization of the chemical components of an aromatherapy recipe. The formulation consisted of four blended essential oils; rosemary oil, eucalyptus oil, pine oil and lime oil (volume ratio 6 : 2 : 1 : 1). The single and combination essential oils were identified by gas chromatographymass spectrometry (GC-MS). The analysis of GC-MS data revealed that several components exist in the mixture. The five most important components of the blended essential oils were 1,8-cineole (35.6 %), α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…These compounds can be quickly evaporated at room temperature due to their volatility, and they are responsible for the characteristic aroma present in LEO. The results obtained in this work are in agreement with previous chemical compositions identified by other authors [ 7 , 18 ], who reported the presence of alkaloids, mono and sesquiterpenoids, acyclic and cyclic hydrocarbons, phenolic and polyphenolic derivatives and their oxygenated derivatives [ 6 , 34 , 35 , 36 ]. EOs composition and concentration of ingredients depend on different factors, such as geographical distribution; citrus variety and environmental conditions such as temperature, precipitations, hours of sunshine and altitude [ 34 ].…”
Section: Resultssupporting
confidence: 93%
“…These compounds can be quickly evaporated at room temperature due to their volatility, and they are responsible for the characteristic aroma present in LEO. The results obtained in this work are in agreement with previous chemical compositions identified by other authors [ 7 , 18 ], who reported the presence of alkaloids, mono and sesquiterpenoids, acyclic and cyclic hydrocarbons, phenolic and polyphenolic derivatives and their oxygenated derivatives [ 6 , 34 , 35 , 36 ]. EOs composition and concentration of ingredients depend on different factors, such as geographical distribution; citrus variety and environmental conditions such as temperature, precipitations, hours of sunshine and altitude [ 34 ].…”
Section: Resultssupporting
confidence: 93%
“…Pine essential oils are most frequently used as perfume and repellent ingredients. Turpentine is used for manufacturing many cosmetics, air fresheners and aromatherapy products [ 77 , 78 , 79 ]. The product that remains after distillation is the rosin that is a non-volatile fraction of oleoresins.…”
Section: Essential Oilsmentioning
confidence: 99%
“…α-Terpineol is also applied in aromatherapy formulations. This monoterpene was present, for instance, in the five most important components of pine oil (20.50%, second most abundant) and lime oil (7.6%, third most abundant) used in aromatherapy (Tadtong et al 2015).…”
Section: Current Market and Applicationsmentioning
confidence: 99%